Physicochemical Properties of Mangifera indica cv. Harumanis Pastille - Farah Afiqah Mohd Zukry (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To optimize the Harumanis ingredient to make pastille using response surface methodology. To evaluate the nutritional content and physicochemical properties of the pastille strengthened with Harumanis powder. To assess the sensory evaluation of Harumanis pastille for overall acceptance.